The relationship between marketing mix and consumer preference in supplement product usage - Sulaiman, Yaty; Masri, Maisarah; Othman, Maha Mohammed Yusr; Ismail, Mohd Yusri Shahril; Mustafa, Saed Adnan; Salim, Nooraini (Serials Publications Pvt. Ltd., 2017)
Nowadays, we can see the entrepreneurs of supplements and cosmetics are also expanding rapidly.Supplement product marketing activities in Malaysia showed significant growth over the past few decades.Based on the Euromonitor, (2015) Gross Domestic Product (GDP) of the health of consumers in Malaysia are experiencing a slow reduction of 5% in 2015 compared to 2014 by 6%. This strong growth has led to questions about the true potential of marketing to further improve the reliability of the product on the consumer preferences of supplements among university students